Diseño de un sistema de gestión de los carritos portaequipajes en un aeropuerto - Vera-Soto, Pablo; Cantizani-Estepa, Juan; Fortes-Rodríguez, Sergio; Barco-Moreno, Raquel (My University, 2022)
Collecting luggage trolleys at an airport poses aproblematic that is usually done in a very inefficient way dueto the lack of information about the position and state of thetrolleys. In this sense, a management system for the luggagetrolleys using NB-IoT and BLE is proposed. Based on a capillaryarchitecture, this system can track the trolleys and distinguishthrough some sensors whether they are being used or not, aswell as if they are in their correspondent storage and displaysthe information in a dashboard created with Grafana.
Keywords: Internet de los objetos; Equipaje -- Gestión; Aeropuertos; IoT; BLE; Bluetooth; Trolley; Sistema de gestión